Tradisi Pernikahan Adat Banggala ditinjau dari Teori Kepatuhan Hukum: Studi Implementasi Undang-Undang No 16 Tahun 2019 - Dimas yusup Hartomo; Moh. Nurhakim; R. Tanzil Fawaiq S. (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The matter of marriage involves various traditions in different regions based on their respective customs and beliefs, which may not necessarily adhere to Islamic law. Marriages within communities sometimes still involve the union of family members. One such village, Kampung Banggala, continues to practice marriages involving individuals under the age of 19. This research employs a qualitative research design with a sociological legal approach to analyze issues within the community. The research instruments include observation, documentation, and interviews. The findings indicate that the residents of Kampung Banggala still adhere to Sharia law, allowing marriages when individuals reach the age of maturity and express interest in the opposite gender. The occurrence of marriages in Kampung Banggala is attributed to parental matchmaking, aimed at maintaining family ties, and a desire for proximity when their children establish their own households. The compliance with legal norms in the community is analyzed through three indicators: the knowledge and understanding of the community, the importance attached to the enforcement of the law, and the tranquility in their lives. In conclusion, the researcher finds that marriages in Kampung Banggala, Kalijati Subang, remain guided by Hadith and the Sunnah of the Prophet. Therefore, they marry off their children in accordance with Sharia when they reach maturity.